The Role of Midwife in Community Empowerment About Early Detection of Pregnancy Complication in Proppo Public Health Center of Pamekasan - Yulia Paramita R.; Yuly Peristiowati; Byba Melda Suhita (Health Notions, 2018)
Every pregnant woman would face the risk of life-threatening complications. WHO estimated that about 15% of all pregnant women would develop into complications related to their pregnancies. The purpose of this research was to explore the role of midwife in community empowerment about early detection of pregnancy complication at Proppo Public Health Center of Pamekasan Regency. This research was a qualitative research. Data collection using primary and secondary data and conducted in-depth interview. Respondent in this research was village midwife at Proppo Public Health Center as many as 17 people. The results showed that midwife's role in community empowerment about early detection of pregnancy complication at Proppo Public Health Center was varied. Village midwives at Proppo Public Health Center served as educators, counselors, facilitators are possible depending on the level of knowledge and education of the community include cadres, community leaders, pregnant women and families. Based on this research, socio-cultural role is very influential on the pattern of empowerment. So it needs to be studied more deeply about socio-cultural factors in relation to community empowerment about early detection of pregnancy complications. Keywords: midwife; pregnancy; complication; society